It should be for people themselves whether they want to take part or not. The organisation should not get involved - a response to Williams - Garcia Iriarte, Edurne (My University, 2019)
In 2019, one of the academic supporters of the IRN was invited to write an article about gatekeepers in research. She asked the IRN members if we wanted to write the article together and a few of us agreed. This article was a response to another article written by Peter Williams. Gatekeepers are people who control contact between people. For example staff working in services often decide if a researcher can talk to people with learning disabilities.
PUBLISHED
Keywords: Inclusive Society; INTELLECTUAL DISABILITY; Inclusive research; gatekeepers